HumanCentred Design: What's Happening in African Industry? - (:unkn) unknown (My University, 2013)
There has been much written about the current 'state of the art' of user experience (UX) and interaction design in the both the academic and the business press in North America and Europe. But where is the African voice? What is happening in these fields in Africa? This panel is intended to explore the African playing field of UX and interaction design. The panellists are all well-known and well-respected within the field and within Africa. We plan to discuss what we see as the current 'state of the art' as well as the challenges, especially the unique challenges, and opportunities that we face in advancing this profession within Africa.
Keywords: African Research